Talak taklik menurut fiqah: analisis pelaksanaannya dalam undang-undang keluarga Islam serta arahan amalan Jabatan Kehakiman Syariah Malaysia = Conditional divorce in Islamic jurisprudence: an analysis of its application in Islamic family law and the practice direction of the Department of Syariah Judiciary Malaysia - Sitiris, Miszairi; Mat Jubri@Shamsuddin, Mustafa; Zakaria, Mohamad Sabri; mokhtar, mohd na'im (Dewan Bahasa dan Pustaka, 2021)
This article studies the hidden wisdom behind the pronouncement of conditional divorce, the rules and conditions prescribed by the jurists, as well as the forms and types of ta’līq in shariah law. This article also seeks to look at the practice of ta’līq in Malaysia as well as provisions under Islamic family law in Malaysia, as well as the Practice Direction issued by the Department of Syariah Judiciary Malaysia. The study employed library research to expound the opinions of earlier jurists from various schools of Islamic jurisprudence, and textual studies on the provisions of law related to the issue concerned. The study found that the wording of the official pronouncements of ta’līq varies from state to state, hence the consequences can also differ. The researcher is of the view that the practice of pronouncing ta’līq after the solemnization of a marriage contract should be reviewed. It needs to be said that the validation of a divorce by ta’līq is a more complicated process than an ordinary divorce.